2018
DOI: 10.1007/s11064-018-2477-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Striatal Nitrosative Stress and Impaired Social Recognition Memory Are Not Magnified by Paraquat Coexposure

Abstract: Systemic inflammation triggered by lipopolysaccharide (LPS) administration disrupts blood-brain barrier (BBB) homeostasis in animal models. This event leads to increased susceptibility of several encephalic structures to potential neurotoxicants present in the bloodstream. In this study, we investigated the effects of alternate intraperitoneal injections of LPS on BBB permeability, social recognition memory and biochemical parameters in the striatum 24 h and 60 days after treatments. In addition, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This study was planned to check if minor inflammatory processes and oxidative insults, that often pass unattended with medical help, could contribute to the slowly progressing neurodegenerative processes, similar to PD. Therefore, the doses of LPS (10 μg/kg) used here were small, as compared to the previous studies (1–7 mg/kg, own data not shown and [ 30 ]), and did not induce any sickness behavior.…”
Section: Discussionmentioning
confidence: 77%
“…This study was planned to check if minor inflammatory processes and oxidative insults, that often pass unattended with medical help, could contribute to the slowly progressing neurodegenerative processes, similar to PD. Therefore, the doses of LPS (10 μg/kg) used here were small, as compared to the previous studies (1–7 mg/kg, own data not shown and [ 30 ]), and did not induce any sickness behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Gonçalves et al (2018) administered 5 mg/kg of paraquat intraperitoneally on the 2nd, 4th, 6th, and 7th day in Swiss male mice. Their data for open-field, rotarod, neurological severity score, and social recognition tests revealed that the systemic administration of lipopolysaccharide (3, 5, and 7 mg/kg, intraperitoneally) induced slower social recognition behavioral deficit and striatal stress in adult mice [ 183 ]. Chinta et al (2018) administered a cumulative of 42 mg/kg of paraquat intraperitoneally (7 mg/kg at two-day intervals for a total of six doses) in C57Bl6/J (p16-3MR) mice models.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…Multiple organs such as liver, kidney, heart and central nervous system can be affected; but lung is the primary target of PQ [ 14 , 20 ]. PQ is actively taken up in a concentration dependent manner and accumulates at particularly high levels in Clara cells and epithelial cells [ 5 , 10 , 13 , 18 ]. PQ poisoning initially leads to acute lung injury (ALI), and ultimately to lung fibrosis or subsequent respiratory failure, which is the most common cause of death from PQ [ 12 ].…”
Section: Introductionmentioning
confidence: 99%